My little learner: E-learning wonderland - Teoh, Wei En (2025)
This project focuses on creating a complete kindergarten e-learning application called "My Little Learner: E-Learning Wonderland", intended to improve early childhood education using digital methods. The main goal is to overcome the shortcomings that currently exist in e-learning platforms for young learners, including inadequate motivation incentives, a lack of a dashboard that provides insight, an absence of a reminder notification system, insufficient support for a variety of learning methods, and a lack of interactive areas. A range of instructional materials catered to the requirements and learning preferences of children in kindergarten will be available on the app. The emphasis will be on providing an exciting and inspiring experience through interactive games, storytelling, and multimedia activities. The app will also use adaptive learning algorithms to tailor the instructional material to each child's unique learning style and speed. Creating an analytic dashboard, which offers information on the child's learning, is a crucial component of the project. This feature will make it easier for kindergarten kids and parents to monitor the learning progress and identify areas for improvement, which will improve the learning process overall. The project will use cutting-edge programming technologies, including Flutter (Dart), Firebase, and Visual Studio Code, to produce an interactive, user-friendly, and flexible learning app that supports various devices. In summary, the project seeks to develop e-learning software for kindergarten that is not only advanced in terms of technology but also sound in terms of education and designed with the unique requirements of young learners in mind. A fully working e-learning app with various instructional activities and extensive support resources to assist teachers and kindergarten children is an anticipated outcome. Area of Study (Minimum 1 Maximum 2): Mobile Application Development, Educational Technology Keywords (Minimum 5 Maximum 10): Kindergarten E-Learning, Mobile Learning Application, Adaptive Learning, Gamified Education, Early Childhood Education